Combining Organic and Foliar Fertilization to Enhance Soil Fertility and Mitigate Physiological Disorders of Durian (Durio zibethinus Murr.) Fruit in the Tropics - Le Van Dang; Nguyen Kim Quyen; Ngo Phuong Ngoc; Le Minh Ly; Pham Thi Phuong Thao; Ngo Ngoc Hung (Plants)
Physiological disorders (PDs) in durian lead to reduced commodity prices; therefore, reducing the PD rate in durian enhances the fruit’s value and farmers’ profits. Nutrient and soil management may affect the PD rate during fruit development. Herein, we used amendments such as organic manure (OM) and foliar fertilization (FF) applications to reduce the PD rate and improve the soil health and fruit yield of durian. This study was conducted in three durian orchards in the Vietnamese Mekong Delta from 2022 to 2024. The treatments were as follows: (i) control (unamended), (ii) OM, (iii) FF, and (iv) OM + FF. N−P−K fertilizers (0.45 kg of N, 0.45 kg of P, and 0.45 kg of K per tree) were uniformly applied to all durian trees. We measured the characteristics of the soil, such as the soil pH, soil organic carbon (SOC), available phosphorus (AP), and exchangeable cations (K+ and Ca2+). The leaf nutrient (K and Ca) content, fruit yield (kg tree−1), and fruit quality (PD rate, total soluble solids (TSS), and aril color characteristics) were also recorded. Our study indicates that OM + FF increased soil pH and SOC, AP, and exchangeable cations (K+ and Ca2+). In addition, the K and Ca concentrations in durian leaves increased by approximately 4% using OM + FF. Combining OM and FF decreased the PD rate of durian fruit (>85%) compared with the control. This practice increased the fruit quality TSS (13%), color, proportion of arils, and fruit yield (~10%) compared with conventional practice (control). Overall, using OM and FF contributed to improving durian production and values. Therefore, we recommend that farmers who cultivate durian apply OM + FF to their orchards to enhance soil health, fruit quality, and yield.